Economic evaluation of dyslexia intervention. (29th October 2022) - Moll, Kristina; Georgii, Beatrice J.; Tunder, Ralph; Schulte‐Körne, Gerd
Abstract : In many countries, intervention costs are not covered by public health care. A critical basis for deciding whether an intervention is covered or not is to analyse the relation between benefits and costs of the intervention, and to quantify the consequential costs. In this study, a cost‐utility analysis was computed to investigate the costs of individualized dyslexia intervention while quantifying the benefit in terms of health‐related quality of life in a sample of 36 individuals with dyslexia. In addition, educational outcomes and costs of untreated dyslexia for the society were estimated using information for class repetition, school success, and unemployment rates from previous studies and official statistics. A significant increase in quality of life with medium effect sizes was found across all quality‐of‐life measures. Increases in quality of life were domain‐specific, thus occurring specifically in those domains that are affected by learning disorders. The cost‐utility ratio was 9, 782 Euros per quality adjusted life years (QALYs), which is in line with similar therapy forms, such as speech therapy. The loss of productivity for untreated dyslexia in the German population was estimated for class repetition and reduced income due to lower school degrees. The cost‐utility analysis and the calculation of consequential costs suggest that the dyslexia intervention is cost‐effective.